Bioinspired model complexes for vanadium haloperoxidases - Nica, Simona Filofteia (2005)
Synthesis and structural characterization of monooxo-and cis -dioxovanadium(v) complexes based on tridentate N-salicylidene carbonic acid hydrazide ligands are reported. By functionalization of the aliphatic side-chain of the chelate system, vanadium(v) compounds were obtained, which structurally mimic some of the hydrogen bonding interaction of the prosthetic group with the protein environment in vanadium-haloperoxidase enzymes. The vanadium model-complexes catalyze the bromination of an activated aromatic system (such as 1,3,5-trimethoxybenzene) in the presence of tetrabutylammonium bromide and hydrogen peroxide, thus mimicking the oxidative halogenation function of the native enzyme. In addition to bromide oxidation, the vanadium(v) complexes, particularly the cis -dioxovanadium(v) species have also shown to oxidize phenyl methyl sulfide to the corresponding sulfoxide. The relevance of these reactions to the mechanism of vanadium haloperoxidases, and moreover the capacity of the peroxovanadium complexes to intermediate the two catalytic reactions will be discussed. In addition binuclear cis -dioxovanadium(v) and cis -dioxomolybdenum(vi) complexes as high effcient catalysts for oxidation of organic sulfides by hydrogen peroxide will be also described.